Comparative evaluation of dimensional stability and flexural strength of different light cured tray materials with self-cured tray material: an in-vitro study - Dr Taha Attarwala; Dr Ramandeep Dugal; Dr Aamir Godil; Dr Sanaa Wadwan; Dr Pallavi Madanshetty; Dr Arshi Kazi (University Library System, University of Pittsburgh, 2022)
Objectives: To carry out a comparative evaluation of dimensional stability and flexural strength of different light cured tray materials with self-cured tray material as control. Materials and methods: The study was carried out in four groups based on the different available tray materials. Group A (n=30) - light cured resin (Individo Lux-VOCO™ GmbH Germany); Group B (n=30)- light cured resin (Profibase-VOCO™ GmbH Germany); Group C (n=30)- light cured resin (Plaque Photo-Willmann and Pein™ GmbH Germany); Group D (n=30)- control group-self cured resin (Asian special instant tray material Asian Acrylates™, Mumbai, India). A digital micro-meter was used to measure the length of each specimen first at 1 hour, 24 hour and 48 hour and three readings were taken up to 0.001 decimal. The values for flexural strength of each specimen were measured using the 3-point bending technique with the help of a universal testing machine. The mean values of dimensional stability and flexural strength were calculated by the one-way ANOVA and Tukey's post-hoc test for multiple group`s comparison. Results The mean change in length (in mm) of light cured resins samples were significantly lower than self-cured resin samples at all three time intervals. The flexural strength values of light cured resin samples-Group A (84.46±13.32 N/mm2), B (83.43±14.52 N/mm2) and C (86.80±14.73 N/mm2) was significantly higher than the self-cured resin samples group D (41.29±7.93 N/mm2) Conclusions: Light cured tray materials are more dimensionally stable and have a higher flexural strength compared to self-cured tray materials.